2020
DOI: 10.5194/gmd-13-1545-2020
|View full text |Cite
|
Sign up to set email alerts
|

P-model v1.0: an optimality-based light use efficiency model for simulating ecosystem gross primary production

Abstract: Abstract. Terrestrial photosynthesis is the basis for vegetation growth and drives the land carbon cycle. Accurately simulating gross primary production (GPP, ecosystem-level apparent photosynthesis) is key for satellite monitoring and Earth system model predictions under climate change. While robust models exist for describing leaf-level photosynthesis, predictions diverge due to uncertain photosynthetic traits and parameters which vary on multiple spatial and temporal scales. Here, we describe and evaluate a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
233
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(244 citation statements)
references
References 188 publications
(180 reference statements)
4
233
0
Order By: Relevance
“…This is why it has been considered to be a value optimized by natural selection (Prentice et al ., 2014). The C i / C a ratio is also a pivotal physiological variable for the coupling of transpiration and photosynthesis from vegetated surfaces in relation to climate in Earth System Models (ESMs) (Wang et al ., 2014; Stocker et al ., 2020). The impact of soil environment on biophysical–biochemical interactions and C i / C a variation is expected to be substantial but has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…This is why it has been considered to be a value optimized by natural selection (Prentice et al ., 2014). The C i / C a ratio is also a pivotal physiological variable for the coupling of transpiration and photosynthesis from vegetated surfaces in relation to climate in Earth System Models (ESMs) (Wang et al ., 2014; Stocker et al ., 2020). The impact of soil environment on biophysical–biochemical interactions and C i / C a variation is expected to be substantial but has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated dominant hydro-meteorological controls of vegetation productivity at a global scale and across different ecosystems (Nemani et al, 2003;Beer et al 2010;Jung et al 2011;Seddon et al, 2016;Madani et al, 2017;Jung et al, 2017;Walther et al, 2019;Li & Xiao, 2020). While these studies and recent gross primary production (GPP) estimates agree that vegetation in (semi-)arid area is significantly impacted by soil moisture (SM) (Stocker et al, 2018;Stocker et al, 2020), a corresponding global analysis including the impact of SM from multiple depths is lacking. Several studies have already highlighted the local relevance of multi-layer SM to ecosystems: root water uptake from deeper soil layers can help mitigate water stress and maintain plant transpiration (Schulze et al, 1996;Migliavacca et al, 2009); A et al, 2019 demonstrated varying relative importance of surface SM versus deeper SM depending on land cover types; and Schlaepfer et al, 2017 simulated an increased dryness of sub-surface SM compared to surface SM which largely impacted vegetation dynamics in temperate drylands.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon this approach, Wang et al (2017) explicitly optimize photosynthetic capacity (albeit using a separate optimization criterion) and have been successful in predicting the assimilation rates and leaf-internal CO2 concentrations across climatic gradients. However, their model lacks a representation of plant hydraulics, and thus cannot predict plant responses to soil drought, especially when soil and atmospheric water deficits are decoupled (Stocker et al, 2018(Stocker et al, , 2020. Here, we extend the foundational principles of Wang et al (2017) with the principles of plant hydraulics and recast them in a profit-maximization framework.…”
Section: Introductionmentioning
confidence: 99%